Cardio-toxicity: Importance of biomarkers - Kostadinović, Jelena; Popadić, Višeslav; Klašnja, Slobodan; Klisić, Aleksandra; Kotur-Stevuljević, Jelena; Andrić, Zoran; Zdravković, Marija (Archives of Pharmacy, 2023)
The clinical efficacy of chemotherapy, as a recognized therapeutic approach for malignant diseases, usually has certain limitations due to its cardiotoxicity (CT) and consequent cardiomyopathy, or even heart failure. CT is defined as any cardiac injury connected with oncology treatment, whether it is chemo-, radio-, targeted or immunotherapy, or cancer by itself, and it represents a great challenge for clinicians in everyday practice. A wide spectrum of factors related to chemotherapy (type of drug, dose during each cycle, cumulative dose, schedule, method of application, combination with other cardiotoxic drugs or association with radiotherapy) and patient characteristics (age, presence of cardiovascular risk factors, previous cardiovascular disease) are the determining factors that influence the frequency of CT. Imaging methods for morphological and functional monitoring of the heart muscle are used for monitoring CT. The quest for diagnostic tools for early CT detection is of great significance. In line with this, the measurement of some cardiac biomarkers has found its place in clinical settings as an early determinant of myocardial injury. Therefore, in this review article, special attention will be paid to certain well-established, as well as certain novel cardiac biomarkers, and their role in recognizing asymptomatic CT, in order to gain deeper insight into their diagnostic utility.
Keywords: cardiotoxicity biomarkers; anthracyclines; trastuzumab